Analisis Partisipasi Masyarakat dalam Program Pengelolaan Sampah Sungai Semangir Kecamatan Mangli Kabupaten Jember - Mawan Defriatno; Aulia Rasul Nur Insan Kamil; Dimas Fahrian; Hesti Mewah Indah Ayu (BIOSAPPHIRE: Jurnal Biologi dan Diversitas, 2023)
Rivers are an important element that connects urban and rural environments which are used by humans and other living creatures. Any action taken on a river will have the effect of changing its nature and condition as an adjustment to the treatment it receives. Community participation can be divided into several forms, namely community participation in planning development programs, community participation in realizing the results of plans made, community participation in utilizing the results of development that has been implemented, and community participation in evaluation which is realized by assessing and supervising development activities and the results. Community participation is influenced by two main factors, namely internal factors and external factors. Internal factors are the social and economic conditions of the community. External factors that influence participation include communication, community leaders, and opportunities to participate. The research was conducted using a deductive approach which uses logic to draw conclusions based on the observations made. The type of research used is qualitative research. Community participation is influenced by 2 main factors, namely internal factors and external factors. Internal factors are the social and economic conditions of the community. External factors that influence participation include communication, community leaders, and opportunities to participate. The River Management Program in the Semanggir River, Jember Regency is to create a clean river program. The Clean River Program (PROKASIH) was formed to control river water pollution and improve river water quality. To support the realization of the program, a River Working Group was formed which will take part in protecting rivers as well as developing the values ??of mutual cooperation and community as well as increasing community participation in river protection and conservation. To increase community participation and the active role of safeguarding related interests, an approach needs to be taken to provide an understanding that waste is the responsibility of all elements. There is a need for synergy between the elements of the pentahelix, namely the government, private sector, academics, media and society, to jointly address the waste issue in the area considering that this area provides quite a large economic contribution to the local community